The Reliability and Validity of the Caregiver Work Limitations Questionnaire. Issue 1 (January 2015) - Lerner, Debra; Parsons, Susan K.; Chang, Hong; Visco, Zachary L.; Pawlecki, J. Brent
Abstract : Objective: To test a new Caregiver Work Limitations Questionnaire (WLQ). On the basis of the original WLQ, this new survey instrument assesses the effect of caregiving for ill and/or disabled persons on the caregiver's work performance. Method: A questionnaire was administered anonymously to employees of a large business services company. Scale reliability and validity were tested with psychometric methods. Results: Of 4128 survey participants, 18.3% currently were caregivers, 10.2% were past caregivers, and 71.5% were not caregivers. Current caregivers were limited in their ability to perform basic job tasks between mean 10.3% and 16.8% of the time. Confirmatory factor analysis yielded a scale structure similar to the WLQ's. Scales reliabilities (the Cronbach's α) ranged from 0.91 to 0.95. Conclusions: The Caregiver WLQ is a new tool for understanding the workplace effect of caregiving.